STUDY OF ALGAE FROM WASTEWATER TREATMENT PLANTS IN ALMATY AND THEIR ROLE IN BIOMONITORING (Eurasian Journal of Ecology, 2025)
This study is aimed at examining the algal flora inhabiting the water bodies of the wastewater treatment plants in Almaty and their role in biomonitoring. Algal flora, including microalgae and cyanobacteria, play an important role in these ecosystems by performing self-purification functions, regulating biogeochemical cycles, and maintaining the balance between organic and inorganic substances. In this work, a comprehensive analysis of the composition and dynamics of the algal flora was carried out in various wastewater streams: in the sedimentation tank after mechanical treatment, in the wastewater channel after biological treatment, in the equalization basin, and in the Sorbulak retention lake. The results of the study are of practical significance for the development of biomonitoring methods and water resource management in urban agglomerations, as well as for improving the efficiency of the wastewater treatment plants in Almaty. The aim of this study was to investigate the species diversity of the algal flora in the water bodies of Almaty’s wastewater treatment plants and to elucidate their role in biomonitoring.The conducted research has established the key role of algal flora in the processes of biological wastewater treatment and in the biomonitoring of the water bodies of Almaty’s treatment plants and the Sorbulak retention lake. It was found that the dynamics of the species composition of microalgae and cyanobacteria are directly related to the level of pollution in the aquatic ecosystems: in areas with high loads of organic substances, cyanobacteria dominate, whereas as pollution decreases, the proportion of green algae and diatoms increases. Bacteriological indicators confirm the effectiveness of the treatment, with studies of the bacterial composition showing that the number of microorganisms gradually decreases through successive treatment stages.Based on the analysis of the saprobity index, it was established that there is a successive reduction in the level of organic pollution during the water treatment process. In the sedimentation tank, conditions are dominated by polysaprobic states characteristic of water bodies with a high organic load. At the final stage (Sorbulak), a significant decrease in the saprobity index is observed, which indicates the effectiveness of the biological treatment processes and the self-restoration of the aquatic ecosystem.The results of the study confirm that active processes of biological self-purification occur in the water bodies of the wastewater treatment plants and in the Sorbulak retention lake, driven by the development of the algal community. The massive proliferation of certain groups of algal flora at the later stages of treatment is indicative of the stabilization of the biological balance of the aquatic ecosystem.Key words: algal flora, microalgae, biomonitoring, wastewater, bioindication, microalgae indicators of saprobity.